Abundance and density of lesser prairie‐chickens and leks in Texas. (2nd July 2013) - Timmer, Jennifer M.; Butler, Matthew J.; Ballard, Warren B.; Boal, Clint W.; Whitlaw, Heather A.
ABSTRACT Lesser prairie‐chickens (LEPCs; Tympanuchus pallidicinctus) have experienced population declines due to both direct and indirect habitat loss, including conversion of native rangeland to cropland and disturbance from energy development. Our objectives were to 1) determine the current density of LEPC leks and LEPCs within the Texas (USA) occupied range, including areas with high potential for wind‐energy development; and 2) find new leks. To estimate lek and LEPC density, we employed a line‐transect‐based aerial survey method using a Robinson 22 helicopter to count leks. We surveyed 26, 810.9 km of transect in the spring of 2010 and 2011 and we detected 96 leks. We estimated a density of 2.0 leks/100 km2 (90% CI = 1.4–2.7 leks/100 km2) and 12.3 LEPCs/100 km2 (90% CI = 8.5–17.9 LEPCs/100 km2) and an abundance of 293.6 leks (90% CI = 213.9–403.0 leks) and 1, 822.4 LEPCs (90% CI = 1, 253.7–2, 649.1 LEPCs) for our sampling frame. Our best model indicated that lek size and lek type (AICc wt = 0.235) influenced lek detectability. Lek detectability was greater for larger leks and natural leks versus man‐made leks. Our statewide survey efforts provide wildlife managers and biologists with population estimates, new lek locations, and areas to target for monitoring and conservation. © 2013 The Wildlife Society.